Functionalized reduce graphene oxide via click chemistry as antiware additives for lube oil / Nadia Jamal - Nadia , Jamal (2017)
Outstanding properties of reduced graphene oxide (rGO) makes it suitable for application in many areas of developmental interests, especially functionalized lubricant additive. The procedure involved synthesizing graphene oxide (GO) via a modified Hummer’s method, then functionalizing it with alkyne and azide compounds via click chemistry methodology over a copper sulphate catalyst. The physicochemical properties of the functional potential lubricant additives were evaluated using Fourier Transform Infrared Spectroscopy (FTIR), Raman Spectroscopy, X-ray Photoelectron Spectroscopy (XPS), X-ray Diffractometry (XRD), Thermal Gravimetric Analyser (TGA), and Field Emission Scanning Electron Microscopy (FESEM). The performance of the lubricant additive, density, viscosity, total acid number (TAN) and four-ball tests were used to determine the performance of the lubricant, while the Scanning Electron Microscope (SEM) were used to generate the image the worn surfaces post-friction test. This indicates the dispersibility and tribological properties of the F-rGO in base oil. Interestingly, the organic moiety in the functionalized rGO was shown to improve its flexibility and stability, while the rGO itself provides hardness. However, the dispersed F-rGO improved the tribological properties of the resulting lubricant, which reduces both the friction coefficient and wear by 36 % and 24 %, respectively. These values suggested that the improved friction and antiwear properties are due to the functionalized rGO and the thin laminated structure, which is duly confirmed by the XRD and FESEM, respectively. These features also induce low shear stress and prevent direct contact between the metal surfaces according to the friction and wear test.